(untitled) (Международный научный журнал «Инженер», 2026)
This article analyzes the significance of modern equipment in ensuring environmental sustainability and protection. Technologies such as air purification, waste recycling, water resource conservation, and the utilization of renewable energy sources are extensively discussed as means to mitigate environmental issues. The article also provides information on the state policy being implemented in Uzbekistan regarding environmental protection, the declaration of 2025 as the "Year of Environmental Protection and Green Economy," and advanced innovations in this field. This study aims to reveal the potential for effective use of modern technologies in achieving environmental sustainability.